Competitive Dynamic between Individual Behaviors of the Mass Media Industry - Yogi Yunanto; Fendy Suhariadi; Praptini Yulianti (Universitas Warmadewa, 2020)
Competitive behavior is also a major factor in the competitive media industry is now getting very tight. This is caused by the print media competition with online or Internet-based media in getting news and advertising to attract participants from readers. This research method uses historical depth case study intended to produce an institutional explanation of the characteristics of the typical behavior shown by principal component analysis. The study also incorporates the classical approach to the historical focus on qualitative interpretation of data, In order to survive, the print media should be able to maintain the credibility and public trust on the information presented is now more attractive and more accurate. The print media began to be threatened because of the rapid development of emerging online media via internet access has encouraged people to seek to access online media simply and easily via mobile phones or gadgets. Connoisseurs of the print media loyal readers will turn to online news media. Reality has happened would threaten the print media industry, but the print media already have the characteristics of the first, namely: the news that is always clear, complete and detailed, online media faster and more sophisticated to broadcast news and always up to date but the online news can only be enjoyed by using the sophisticated tool not all communities have the tools and not all people can use sophisticated technology to always follow the news online.